Analysis of Drive-Thru Service Innovation in the Motor Vehicle Tax Collection System to Improve Tax Compliance in Manyar, Surabaya (A Social Science and Entrepreneurship Journal, 2025)
This study aims to analyze the implementation of the SamsatDrive-Thru service innovation in the Motor Vehicle Tax (PKB)collection system at Samsat Manyar Surabaya and its impacton improving taxpayer compliance. This service wasintroduced to address long queues and complicatedpayment procedures. The research uses a mixed method,namely quantitative and qualitative, with data collectiontechniques in the form of interviews, observations, andanalysis of tax revenue data. The results of the study indicatethat the Samsat Drive-Thru service has a positive impact ontaxpayer compliance. The ease and efficiency of the paymentprocess encourage taxpayers to pay their taxes on time. Inaddition, there has been an increase in PKB revenue afterthis service was implemented. This service is consideredsuccessful in simplifying bureaucratic processes andimproving convenience for the public. The studyrecommends expanding the scope of the Samsat Drive-Thruservice, such as for vehicle registration and ownershiptransfer, to provide broader benefits. Additionally, increasedpublic awareness is important to ensure more taxpayers areaware of and utilize this service. With the right strategy, thisinnovation can support improved tax compliance andefficiency in public services related to motor vehicletaxation..
Keywords: Innovation; Drive-Thru Tax Compliance; Tax Revenue Motor Vehicle Tax Samsat Services